Alternative fish feed production from waste chicken feathers - Sri Jumini (International Journal of Science and Applied Science: Conference Series, 2017)
In this This devotion has been done to provide education and training of the utilization of waste chicken manure, making flour chicken feathers as a fish feed alternative, that can overcome some of the problems that waste chicken feathers from the center cutting broiler chickens in the village Krasak enough, it causes pollution, and not used optimally; Low public awareness of awareness of environmental pollution; the lack of public knowledge about the utilization of waste chicken feathers, and processing technology, as well as to address the needs of fish feed more expensive, need alternative feed ingredients. This service program has provided insight to the public about waste chicken feathers so that it can be used as a new entrepreneurial startups. To achieve these objectives have been done of activity as follows: 1) Provide counseling and understanding of the community will be a negative impact on the environment of waste chicken feathers. 2) Provide counseling utilization of waste chicken feathers for people in nearby farms. 3) Make a chicken feather meal of chicken feather waste as an alternative fish feed to improve digestibility of chicken feathers. 3) The formation of the group for increasing the economic income of the family. This service activities program runs quite well with demonstrated some activity, namely: 1) Change Behavior Society (knowledge transfer); 2) Chicken Feather Extension Waste Utilization; 3) Making Unit Waste Chicken Feathers; 4) Establishment of New Business of Diversified Waste Chicken Feathers.